2017
DOI: 10.1080/16506073.2017.1315612
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress in emergency medicine clinicians

Abstract: Previously called Secondary Traumatic Stress (STS), secondary exposure to trauma is now considered a valid DSM-5 Criterion A stressor for posttraumatic stress disorder (PTSD). Previous studies have found high rates of STS in clinicians who treat traumatically injured patients. However, little research has examined STS among Emergency Medicine (EM) physicians and advanced practice providers (APPs). The current study enrolled EM providers (N = 118) working in one of 10 hospitals to examine risk factors, protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
3
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 33 publications
8
58
3
2
Order By: Relevance
“…It is possible that intensive care physicians may not be proficient in the assessment, perception, and interpretation of psychiatric symptoms. Nevertheless, our data are consistent with previous reports of severe stress in intensive care physicians caused by the specific challenges in this area of work (5,60).…”
Section: Private Occupational and Health Situationsupporting
confidence: 93%
“…It is possible that intensive care physicians may not be proficient in the assessment, perception, and interpretation of psychiatric symptoms. Nevertheless, our data are consistent with previous reports of severe stress in intensive care physicians caused by the specific challenges in this area of work (5,60).…”
Section: Private Occupational and Health Situationsupporting
confidence: 93%
“…Personal trauma history, including direct exposure to traumatic events such as childhood abuse, criminal victimization, and natural disaster, has been correlated with increased STS among professionals who work therapeutically with trauma victims (Hensel, Ruiz, Finney, & Dewa, 2015), including child protective services workers (Bride, Jones, & MacMaster, 2007) and emergency medicine clinicians (Roden-Foreman et al, 2017). Research has indicated that any trauma history can increase the risk of STS among care providers, although experiencing a similar type of trauma to the one the individual they are supporting has experienced can be even more deleterious in terms of STS outcomes (Hensel et al, 2015).…”
mentioning
confidence: 99%
“…9 A study of EPs and advance practice providers from a group practice in the U.S. found a PTSD prevalence of 12.7%. 10 Research from other countries corroborates this vulnerability, with prevalence of self-assessed PTSD of 16.8% in German EPs, 15.4% in Pakistani EPs, and 14.5% in Belgian EPs. [11][12][13] The objective of this study was to determine the point prevalence of PTSD in a cohort of practicing EPs from multiple practice settings in the U.S., and to compare this to the prevalence in the general population.…”
Section: Introductionmentioning
confidence: 89%